Effects of early adjunctive pharmacotherapy on serum levels of brain injury biomarkers in patients with traumatic brain injury: a systematic review of randomized controlled studies - Mansour, Noha O.; Elnaem, Mohamed Hassan; Abdelaziz, Doaa H.; Barakat, Muna; Dehele, Inderpal Singh; Elrggal, Mahmoud E.; Abdallah, Mahmoud S. (Frontiers in Pharmacology, 2023)
Objectives: Traumatic brain injury (TBI) is one of the top causes of morbidity and mortality worldwide. The review aimed to discuss and summarize the current evidence on the effectiveness of adjuvant neuroprotective treatments in terms of their effect on brain injury biomarkers in TBI patients. Methods: To identify relevant studies, four scholarly databases, including PubMed, Cochrane, Scopus, and Google Scholar, were systematically searched using predefined search terms. English-language randomized controlled clinical trials reporting changes in brain injury biomarkers, namely neuron-specific enolase (NSE), glial fibrillary acid protein (GFAP), ubiquitin carboxyl-terminal esterase L1 (UCHL1) and/or S100 beta (S100 ß), were included. The methodological quality of the included studies was assessed using the Cochrane risk-of-bias tool. Results: A total of eleven studies with eight different therapeutic options were investigated; of them, tetracyclines, metformin, and memantine were discovered to be promising choices that could improve neurological outcomes in TBI patients. The most utilized serum biomarkers were NSE and S100 ß followed by GFAP, while none of the included studies quantified UCHL1. The heterogeneity in injury severity categories and measurement timing may affect the overall evaluation of the clinical efficacy of potential therapies. Therefore, unified measurement protocols are highly warranted to inform clinical decisions. Conclusion: Few therapeutic options showed promising results as an adjuvant to standard care in patients with TBI. Several considerations for future work must be directed towards standardizing monitoring biomarkers. Investigating the pharmacotherapy effectiveness using a multimodal biomarker panel is needed. Finally, employing stratified randomization in future clinical trials concerning potential confounders, including age, trauma severity levels, and type, is crucial to inform clinical decisions